Disability Studies Meets Microhistory : The Secret Life of Bíbí in Berlín - Stefánsdóttir, Guðrún Valgerður (Taylor & Francis, 2024)
This volume explores the life of Bjargey “Bíbí” Kristjánsdóttir (1927–1999), an Icelandic woman with intellectual disabilities, through analysis of her autobiography and personal archive on the basis of the research disciplines of critical disability studies and microhistory. Bíbí, who grew up in northern Iceland on a small farm called Berlin, fell ill when she was in her first year and was afterward labeled "feeble-minded" by her family and the local community. When Bíbí died, she had finished a 145,000-word autobiography which she had written alone and kept secret from her family and neighbors, very few of whom even knew that she could read and write. This book aims to consider Bíbí’s life through her autobiography and other historical sources she created, to identify how various historical, social, and cultural factors interacted and influenced her circumstances. It explores Bíbí’s agency, and how she managed to play her cards within the narrow scope given to her by society. What makes Bíbí’s history extraordinary is precisely the direct connection to her world through her counter-archive. This book provides students and scholars of the humanities and the social sciences with a new way of critical thinking about both disciplines. The Open Access version of this book, available at http://www.taylorfrancis.com, has been made available under a Creative Commons [Attribution-Non Commercial-No Derivatives (CC-BY-NC-ND)] 4.0 license.